Does Transformational Adaptation Require a Transformation of Climate Services? - Boon, Eva; Goosen, Hasse; van Veldhoven, Felix; Swart, Rob (Frontiers in Climate, 2021)
Cities, regions and countries are increasingly adapting to climate change. Adaptation approaches often build on disaster management activities to deal with climate extremes and make improvements to already existing systems to prepare for climate change, e.g. through water engineering or cooling existing buildings. But ideally, adaptation strategies aim also at tackling the root causes of climate risks through broader sustainable development pathways. Such transformational approaches, however, are still in their infancy. In this perspective paper we argue that there is a lack of guidance to support policy-makers to develop transformational adaptation strategies. There is a need and opportunity to develop climate services that support transformational adaptation. We explore how climate services can support transformational adaptation, drawing from literature, practical experience and illustrative examples. We identify four knowledge requirements: 1) system knowledge to identify the root causes and solutions; 2) inspirational and cross-disciplinary knowledge to develop a long-term vision; 3) a clear climate message and guiding principles to mainstream the vision; and 4) design principles that are connected to the priorities and interests of the stakeholders. We conclude that developing climate services for transformational adaptation involves a delicate process of simplifying and aggregating climate knowledge, as well as integrating it with knowledge about the physical, economic and social systems of cities and regions. This means that climate service providers need to widen their scope and skills, and collaborate with experts in the fields urban planning, landscape architecture, ecology, health and sociology.